The HCV care continuum among people who use drugs: protocol for a systematic review and meta-analysis. Issue 1 (December 2016) - Reed, Jennifer; Jordan, Ashly; Perlman, David; Smith, Daniel; Hagan, Holly
Abstract Introduction The diagnosis, management, and treatment for hepatitis C virus (HCV) infection (the "HCV care continuum") have improved in recent years. People who use drugs (PWUD) have a prevalence of HCV infection from 30 to 70 %, yet rates of testing, engagement in care, and treatment for HCV are disproportionately low compared to other populations. Delineating the progression of PWUD through the steps in the HCV care continuum in the USA is important in informing efforts to improve HCV outcomes among PWUD. Methods/design Scientific databases will be searched using a comprehensive automated search strategy; gray literature and reference lists will be manually searched. Eligible reports will provide original research data related to the HCV care continuum in the USA including proportions of PWUD engaging in the following discrete steps: screening/testing, engagement in care (including receiving an HCV clinical assessment), treatment initiation and completion, and rates of those with successful HCV treatment. A quality-rating tool will be developed to ascertain the level of bias (including selection bias) in each report, and a quality score will be assigned to each eligible report. A tool adapted from the Pragmatic Explanatory Continuum Indicator Summary-2 instrument will be developed to assess the extent to which an included report reflects an effectiveness or efficacy study design. Pooled estimates and measures of association will be calculated using random effects models, and heterogeneity will be assessed at each stage of data synthesis. Discussion Through this review, we hope to quantify the proportion of PWUD at each progressive step and to help identify key individual, social, and structural points of leakage in the HCV care continuum for PWUD. In meeting these objectives, we will identify predictors to progress along the HCV care continuum, which can be used to inform policy to directly improve HCV care for PWUD. Systematic review registration PROSPEROCRD42016034113